Formulierungsmuster auf Dänischer Schildern - Bonner, Maria (Folia Scandinavica Posnaniensia, 2016)
Communication style on signs in public spaces reflects the sociocultural values of a speech community and provides insight into its preferred mode of communication with unknown communication partners. The linguistic routines present in these texts are part of professional linguistic competence. Starting with an inadequate Danish translation of a sign in a German supermarket, this article examines texts on Danish signs with the purpose of identifying and describing the inventory of patterns for this particular genre. Using Sandig’s text linguistic approach, a corpus of about 200 texts was analyzed with respect to the linguistic patterns for regulating behavior or conveying information – the most prominent linguistic actions on signs. The analysis comprises the grammatical forms, the lexical means to characterize the intended message, mitigation strategies, face saving strategies and irony as well as expressions of emotional involvement by the communicator. The results do not allow a general conclusion about preferred patterns but show the potential range of options. Two observations might be pointed out as salient, namely the use of huske ‘remember’ as presequence for getting attention or as part of the proposition and the relative scarcity of mitigating strategies.